Maternal neonaticide, shame and social melancholy in Hsu-Ming Teo's Love and Vertigo - Zhou, Qiaoqiao; Omar, Noritah (Penerbit Universiti Kebangsaan Malaysia, 2023)
Most critics read Love and Vertigo (2000) by Chinese-Australian writer Hsu-Ming Teo as a novel about diaspora and migrancy. However, the recurrent trope of maternal neonaticide has been critically neglected considering Teo’s portrayal of the predicaments of two generations of mothers who either dispose of or kill their neonates. This article refutes the cultural and radical feminists’ reductionist essentialization of maternal morality depicted in most literary works by probing into the ambivalence in motherhood represented by maternal neonaticide in the selected novel. Drawing on Kelly Oliver’s theory of social melancholy, this article critically examines motherhood against the specific sociohistorical context, aiming to deconstruct the stigma and pathology surrounding maternal neonaticide. Oliver proposes that social melancholy stems from one’s inability to mourn the lost lovable self due to the unavailability of positive representation of motherhood in the phallocentric society. Traditional maternal ethics tend to stigmatize or pathologize mothers who kill, which covers up the institutional causes for maternal neonaticide as a symptom of social melancholy. This article interprets maternal neonaticide as a manifestation of what has been suppressed by the hierarchical and phallogocentric discourses. It aims to illustrate that the fictional representation of maternal neonaticide discloses exactly the pathology in the real world that devalues women and deprives them of positive social space for sublimation. It is social melancholy that constructs passive and shameful female bodies that disempower mothers. The article concludes that despite the prevalent literary discourses that assign blame to mothers, it is more constructive to look beyond the text and examine the underlying melancholy of social oppression that internalizes the sense of shame within mothers and impedes their ability to love.